Radical voices, radical ways : Articulating and disseminating radicalism in seventeenth- and eighteenth-century Britain - Smith, Nigel, 1958-; Curelly, Laurent (Book collections on Project MUSE., 2016)
This collection of essays studies the expression and diffusion of radical ideas in Britain from the period of the English Revolution in the mid-seventeenth century to the Romantic Revolution in the early nineteenth century. The essays included in the volume explore the modes of articulation and dissemination of radical ideas in the period by focusing on actors ('radical voices') and a variety of written texts and cultural practices ('radical ways'), ranging from fiction, correspondence, pamphlets and newspapers to petitions presented to Parliament and toasts raised in public. They analyse the way these media interacted with their political, religious, social and literary context. This volume provides an interdisciplinary outlook on the study of early modern radicalism, with contributions from literary scholars and historians, and uses case studies as insights into the global picture of radical ideas. It will be of interest to students of seventeenth- and eighteenth-century literature and history.